Agriculture in the face of changing markets, institutions and policies: Challenges and strategies - Jarmila Curtiss; Alfons Balmann; Kirsti Dautzenberg; Kathrin Happe (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2006)
Since the late 1980s, agriculture in Central and Eastern European Countries (CEECs) has been under considerable adjustment pressure due to changing political, economic and institutional environments. These changes have been linked to the transition process, as well as the ongoing integration into the European Union and the world market. Reduced subsidies, increased environmental and food quality demands, as well as structural changes in the supply, processing and food retailing sector call for major structural adjustments and the improvement of farmers' managerial abilities. Though such changes always carry significant threats to farms, they also offer new opportunities for the farms' entrepreneurial engagement. Upcoming changes in the agricultural environment and their possible consequences for farm structures across Europe are thus still timely subjects. The objective of the IAMO Forum 2006 is to contribute to the success of agriculture in the CEECs, as well as their neighboring countries, in today's increasingly competitive environment. Concrete questions the conference focuses on are: What are the most suitable farm organizations, cooperative arrangements and contractual forms? How to improve efficiency and productivity? Where do market niches lie and what are the new product demands? CONTENT: Preface; Jarmila Curtiss, Alfons Balmann, Kirsti Dautzenberg, Kathrin Happe. The success of gradualism: Empirical evidence from China's agricultural reform; Jikun Huang, Johan F. M. Swinnen, Scott Rozelle. Land reform and farm restructuring in Moldova, Azerbaijan and Kazakhstan: A stocktaking; David Sedik. Land market developments, imperfections, and effects in transition countries; Johan F. M. Swinnen, Pavel Ciaian, Liesbet Vranken. Farmland markets, boom/bust cycles, and farm size; Charles B. Moss, Andrew Schmitz. Duality of farm structure in transition agriculture: The case of Moldova; Zvi Lerman, Dragos Cimpoies. Organizational restructuring of the agrarian sector in Bulgaria during the pre-accession period; Julia M. Doitchinova, Ivan St. Kanchev, Albena Miteva. Governance of Bulgarian farming - Modes, efficiency, impact of EU accession; Hrabrin Bachev. Leadership may have a decisive influence on the successful transition of production cooperatives - A social capital approach; Csaba Forgács. Contractual arrangement and enforcement in transition agriculture: Theory and evidence from China; Hongdong Guo. Contractrual relationships in the Hungarian horticultural sector; Imre Ferto. Contract farming in China: Perspectives of smallholders; Hongdong Guo, Robert W. Jolly, Jianhua Zhu. Are macro policies adjusted to institutional arrangements at the micro level? Some evidence from Polish Agriculture during transition; Jan Falkowski, Dominika Milczarek. The Austrian private foundation as a legal form in farm management, with special emphasis on tax issues; Hermann Peyerl, Günter Breuer. Credit as a tool of integration between the Polish farms and buyers of their products; Alina Danilowska. Who, why and how: Problems of farmers' interest representation in Poland; Aldona Zawojska. How competitive is milk production in the Central and Eastern European countries in comparison to Western Europe? Mikhail Ramanovich, Torsten Hemme. Production and trade of animal products in selected ECO countries; Farhad Mirzaei, Olaf Heidelbach. European agriculture without direct payments - A partial equilibrium analysis; Oliver Balkhausen, Martin Banse. Measuring the degree of market power in the Ukrainian milk processing; Oleksandr Perekhozhuk, Michael Grings. Determinants of foreign direct investments in the food processing industry: An empirical analysis for Ukraine; Oksana Luka. Allocative efficiency of corporate farms in the Leningrad region; David Epstein. Pathways towards efficient levels of machinery investments needed for the sustainable development of arable farms in Bulgaria; Nikolay Naydenov. Small-scale farming in Romania - Shadow prices and efficiency; Johannes Sauer, Borbala Balint. How large is the marginal product of land in the Moscow region? Natalia Il'ina, Nikolay Svetlov. Spatial price transmission on the Turkish wheat market - An initial application; Enno-Burghard Weitzel, Ahmet Bayaner. Farm to retail price transmission on the pork market: A German-Hungarian comparison; Lajos Zoltán Bakucs, Imre Ferto, Heinrich Hockmann, Oleksandr Perekhozhuk. The nature of selected price transmissions in the agri-food chain and their consequences; Lukáš Čechura. Labor mobility in transition countries and the impact of institutions; Thomas Herzfeld, Thomas Glauben. Choosing to migrate or migrating to choose: Migration and labor choice in Albania; Carlo Azzarri, Gero Carletto, Benjamin Davis, Alberto Zezza. Rural non-farm employment in Ukraine; Oleg Nivyevskiy, Stephan von Cramon-Taubadel. Opportunities and challenges for farm household livelihood strategies: Pluriactivity in Finland and the UK; Claire Newton. Territorial aspects of enterprise development in remote rural areas of Europe; Zuzana Bednarikova, Tomas Doucha, Zdenek Travnicek. New policy approaches for rural development: The experience of two case regions in Eastern Germany; Theodor Fock
urn:nbn:de:gbv:3:2-5280
Keywords: 330